My Itinerary - Edmond Jabès (Studies in 20th & 21st Century Literature, 1987)
My Itinerary
Keywords: Edmond Jabès; self-reflection; Jew; Jewish; culture; meaning; writer; auto reflection; Judaism; image; self; God; French poetry